Validitas dan Praktikalitas E-Modul Larutan Elektrolit dan Non Elektrolit Berbasis Guided Discovery Learning untuk Kelas X SMA/MA - Wildayati Wildayati; Yerimadesi Yerimadesi (Universitas Negeri Padang, 2021)
This study aims to analyze the validity and practicality of the e-module being developed. This type of research is research and development (R&D) with the Plomp development model. The e-module validity test was conducted by four lecturers from the Department of Chemistry, Faculty of Mathematics and Natural Sciences, UNP and three chemistry teachers. The practicality test was carried out by three chemistry teachers and 32 grade XI students of SMAN 7 Padang for the 2020/2021 school year. The research instrument used was a validity questionnaire and practicality. The validity results were analyzed using the Content Validity Ratio (CVR) and the practical results used the Aikens'V formula. From the research, it was found that the CVR average value of the e-module content validity was 0,95 (valid), the construct validity was 0,82 (valid), the practicality of the e-module for the teacher was 0,89 (practical) and for the students was 0,82 ( practical). Based on the results of the study, it was concluded that the e-module of electrolyte and non-electrolyte solutions based on guided disscovery learning for class X SMA / MA developed was valid and practical. Penelitian ini bertujuan untuk menganalisis validitas dan praktikalitas dari e-modul yang dikembangkan. Jenis penelitian adalah Research and Development (R&D) dengan model pengembangan Plomp. Uji validitas e-modul dilakukan oleh empat dosen jurusan kimia FMIPA UNP serta tiga guru kimia. Uji praktikalitas dilakukan oleh tiga guru kimia dan 32 siswa kelas XI SMAN 7 Padang tahun ajaran 2020/2021. Instrumen penelitian yang digunakan angket validitas dan praktikalitas. Hasil validitas dianalisis menggunakan Content Validity Ratio (CVR) dan hasil praktikalitas menggunakan formula Aikens’V. Dari penelitian didapatkan hasil nilai rata-rata CVR validitas konten e-modul sebesar 0,95 (valid), validitas konstruk 0,82 (valid), praktikalitas e-modul pada guru 0,89 (praktis) dan pada siswa 0,82 (praktis). Berdasarkan hasil penelitian disimpulkan bahwa e-modul larutan elektrolit dan non elektrolit berbasis guided disscovery learning untuk kelas X SMA/ MA yang dikembangkan telah valid dan praktis.